Cumulus cell expansion and first polar body extrusion during in vitro oocyte maturation in relation to morphological and morphometric characteristics of the dromedary camel ovary. (21st September 2016) - Mesbah, F; Kafi, M; Nili, H
Contents: The morphological and morphometric characteristics of the ovary are fundamental properties for in vitro oocyte maturation. Nuclear maturation, including first polar body (1PB) extrusion, cytoplasmic maturation and cumulus cell (CC) expansion are the criteria for in vitro maturation (IVM) of oocyte. This study was designed to determine the effect of morphological and morphometric features of the ovary on CC expansion and 1PB extrusion during IVM of oocyte in the adult female dromedary camel. The weight, volume and three dimensions of ovaries from slaughtered dromedary camels and oocytes inside zona diameter and zona pellucida thickness were measured. The follicles were classified in regard to the size and oocytes according to their ooplasm appearance and CC compactness. Aspirated cumulus oocyte complexes (COCs) were incubated for 48 hr (with a 6‐hr interval) in Hams‐F10, and CC expansion and 1PB extrusion were assessed. Significant differences were seen in the shape, weight, volume and three dimensions of the ovaries between ≤4‐year‐old and >4‐year‐old dromedary camel ( p < .5). Approximately, 95.82% of follicles were 2–4 mm in diameter. The mean (± SD ) of inside zona diameter of the oocyte and zona pellucida thickness was 132.22 ± 13.8 and 14.64 ± 2.24 μm, respectively, in >4‐year‐old dromedary camel. The CC expansion and 1PB extrusion were seen in 86% and 21.88% of COCs, respectively. Age and sexual conditions of dromedary camel influence the morphological and morphometric characteristics of the ovary. Most COCs retrieved from 2–6 mm follicles are cultivable. The most slaughterhouse‐derived COCs retrieved from 2–6 mm follicles of non‐pregnant dromedary camels are excellent and good and yielding a most favourable diameter to achieve the developmental competence for IVM in an optimal time of 24–30 hr; the optimal time for CC expansion is 24–30 hr in this species. However, the CC expansion is a prerequisite process, but not sufficient for IVM.